2011
DOI: 10.1371/journal.pone.0028325
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Type-3 Matrix Metalloproteinase (MT3-MMP) Functions as a Matrix Composition-Dependent Effector of Melanoma Cell Invasion

Abstract: In primary human melanoma, the membrane-type matrix metalloproteinase, MT3-MMP, is overexpressed in the most aggressive nodular-type tumors. Unlike MT1-MMP and MT2-MMP, which promote cell invasion through basement membranes and collagen type I-rich tissues, the function of MT3-MMP in tumor progression remains unclear. Here, we demonstrate that MT3-MMP inhibits MT1-MMP-driven melanoma cell invasion in three-dimensional collagen, while yielding an altered, yet MT1-MMP-dependent, form of expansive growth behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 52 publications
1
55
0
1
Order By: Relevance
“…We reported that MMP16 functions as a matrix compositiondependent regulator of melanoma cell invasion and 3D growth (16). While promoting fibrin invasion, MMP16 also associates with MMP14 in hetero-oligomers cleaving and posttranslationally suppressing this proinvasive protease (16). These observations suggest an MMP16 function in melanoma pathogenesis.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…We reported that MMP16 functions as a matrix compositiondependent regulator of melanoma cell invasion and 3D growth (16). While promoting fibrin invasion, MMP16 also associates with MMP14 in hetero-oligomers cleaving and posttranslationally suppressing this proinvasive protease (16). These observations suggest an MMP16 function in melanoma pathogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…WM852 and WM165 cells from melanoma metastasis (Wistar Institute, Philadephia, PA), as well as Bowes melanoma cells and COS1 cells (ATCC) were cultivated as described (16,17). Human foreskin lymphatic endothelial cells (LEC; PromoCell), and blood endothelial cells (BEC; dermal HDBECs and umbilical vein endothelial cells HUVECs, PromoCell) were cultured in Endothelial Cell Growth Medium MV containing gentamicin (50 mg/mL).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…MMP16 was originally cloned from a human placenta cDNA library, and was demonstrated to be located in the cell membrane (13). MMP16 exhibits a high expression level in a variety of tumors tissues, including gastric cancer, astrocytoma and melanoma, compared with normal tissues (14)(15)(16), indicating its potential biological function. A previous study reported that the migration and invasion of gliomas was mediated by MMP16 (17), which indicated that the expression of the MMP16 gene may be associated with tumor cell invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%